Hot off the Press. Issue 12 (28th November 2019) - Hill, Robert A.; Sutherland, Andrew
Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as burlemarxione A from Clusia burle-marxii. Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as burlemarxione A from Clusia burle-marxii.